1974
DOI: 10.1037/h0036884
|View full text |Cite
|
Sign up to set email alerts
|

Modification of affective consequences of alcohol: A comparison of social and solitary drinking.

Abstract: Using Schachter's theory of emotion as a starting point, two predictions regarding the interaction of alcohol consumed in social and solitary situations were tested experimentally. It was predicted that the cognitive circumstances of social drinking would promote an affective response to alcohol, whereas the same objective level of intoxication would be responded to as physical symptoms among solitary drinkers. Additionally, it was predicted that the social manipulation would be effective only to the extent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 10 publications
5
82
0
1
Order By: Relevance
“…Consistent with the findings of Pliner and Cappell (1974), my colleagues and I have been guided by the premise that to comprehensively identify the effects of alcohol on positive affect in social drinkers, one must evaluate such participants in a social context (Sayette et al, 2012a). Further, in light of the reliably observed effects of alcohol in unstructured social interactions and the inconsistent data found during scripted interactions employing confederates (Fairbairn & Sayette, 2014), our approach investigates the impact of alcohol on initial group formation using groups of unacquainted participants interacting in an unscripted setting.…”
Section: Emotional Enhancementmentioning
confidence: 93%
See 1 more Smart Citation
“…Consistent with the findings of Pliner and Cappell (1974), my colleagues and I have been guided by the premise that to comprehensively identify the effects of alcohol on positive affect in social drinkers, one must evaluate such participants in a social context (Sayette et al, 2012a). Further, in light of the reliably observed effects of alcohol in unstructured social interactions and the inconsistent data found during scripted interactions employing confederates (Fairbairn & Sayette, 2014), our approach investigates the impact of alcohol on initial group formation using groups of unacquainted participants interacting in an unscripted setting.…”
Section: Emotional Enhancementmentioning
confidence: 93%
“…Surprisingly, however, these social drinking participants often find themselves drinking in isolation in the laboratory (Fairbairn & Sayette, 2014). In a study that should have done more to reposition the field, Pliner and Cappell (1974) contrasted the effects of alcohol while consumed alone to those observed while in groups. Participants drinking in groups reported and displayed changes that were primarily emotional (e.g., feeling less unhappy), while those consuming alcohol in isolation reported primarily physiological changes (e.g., feeling dizzier).…”
Section: Emotional Enhancementmentioning
confidence: 99%
“…The findings contribute to an existing literature that suggests social context plays an important role in the subjective effects of drugs. For instance, in humans alcohol consumption in the presence of peers is more pleasurable than drinking alone (Adesso, 1985;Pliner & Cappell, 1974;Smith et al, 1975). In animals, social interaction can attenuate an alcohol aversion (Gauvin et al, 1994), and can influence the general responsiveness and sensitivity to alcohol (Varlinskaya et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies have assessed the differences in consumption between solitary and social drinkers, and found that those in a group drink more than those who are alone (Lindman, 1982). Mood changes can also be influenced by social setting, with lone drinkers reported less euphoria and more aversive subjective effects of alcohol than those drinking in company (Lindman, 1982;Pliner and Cappell, 1974). Responses to alcohol in the lab may also be influenced by the instructions ⁄ information given by the experimenter.…”
mentioning
confidence: 92%